The Influence of Corporate Governance and Executive Compensation on the Likelihood of Financial Statement Fraud: Empirical Study on Property, Real Estate, and Construction Companies Listed on the IDX in 2019-2021 - Setyarahman, Astrid Ariyani; Januarti, Indira (GoAcademica Research & Publishing, 2025)
This study aims to obtain empirical evidence and analyze the effect of corporate governance such as the independent board of commissioner, the number of board meetings, the age of the board of commissioners, the financial and/or accounting expertise of the board of commissioners, the independent audit committee and executive compensation on financial statement fraud. The sampling method used is purposive sampling. Secondary data is obtained from annual financial reports for the 2019-2021 period with certain characteristics. Samples are obtained from Bloomberg data or obtained directly from the company's official website. The sample data that met the criteria in this study were 205 companies. The analysis technique used is logistic regression analysis and the data processing tool uses SPSS V26. The results of this study indicate that the independent board of commissioners and executive compensation have a negative effect on the possibility of fraudulent financial statements. Meanwhile, board of commissioner meetings, board of commissioners age, board of commissioners financial and/or accounting expertise, audit committee have no effect on the possibility of fraudulent financial statements.